Tindak Tutur Ilokusi Dalam Lagu “Lughāt al-ʻĀlam” Karya Humood Alkhuder : Kajian Pragmatik - Fadila, Nur; Ekawati, Ekawati (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2026)
Language functions not only as a means of communication, but also as an instrument of action that represents the speaker’s intentions, feelings, and inner experiences. In the realm of art, particularly music, language is expressed through song lyrics that carry meaning as well as specific communicative acts. This study aims to analyze the meanings of locutionary and illocutionary acts in the song “Lughāt al-ʻĀlam” by Humood Alkhuder by applying a pragmatic approach based on speech act theory proposed by J.L. Austin and further developed by John Searle. This research employs a descriptive qualitative design using a library research method and document analysis technique. The primary data consist of the song lyrics, while secondary data are drawn from books, articles, and academic journals related to pragmatics. The findings indicate that the lyrics contain illocutionary acts that function to praise, express affection, and convey respect. Therefore, the language used in the song does not merely communicate lexical meaning, but also reflects complex communicative actions that generate emotional impact.